Detection of the signatures of earthquake preparation with an epicentre in a seismic region by the MCSM NSAU seismic array - Yu. Gordienko (Ukrainian Antarctic Journal, 2010)
In article review the possibility of a seismic array of MCSM NSAU in detection of the seismic region mode changes, related to the earthquake preparation.